2017
DOI: 10.1590/1678-4685-gmb-2016-0128
|View full text |Cite
|
Sign up to set email alerts
|

Papillomaviruses: a systematic review

Abstract: In the last decades, a group of viruses has received great attention due to its relationship with cancer development and its wide distribution throughout the vertebrates: the papillomaviruses. In this article, we aim to review some of the most relevant reports concerning the use of bovines as an experimental model for studies related to papillomaviruses. Moreover, the obtained data contributes to the development of strategies against the clinical consequences of bovine papillomaviruses (BPV) that have led to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 247 publications
(518 reference statements)
1
81
0
7
Order By: Relevance
“…ese clinical presentations are in agreement with the previous observations reported by another researcher [20]. Moreover, Araldi [2] found that papillomatosis might be a severe problem of cattle herds if a large number (20-25%) of young cattle were infected [8]. e results of this study showed the detection of papillomatosis between a male calf presented with multiple body lesions and two females.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ese clinical presentations are in agreement with the previous observations reported by another researcher [20]. Moreover, Araldi [2] found that papillomatosis might be a severe problem of cattle herds if a large number (20-25%) of young cattle were infected [8]. e results of this study showed the detection of papillomatosis between a male calf presented with multiple body lesions and two females.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, malnutrition, hormonal imbalances, artificial insemination, long-term exposure to sunlight accompanied with immunodeficiency, and contaminated utensils such as milk machines and syringes are all factors that play an important role in the occurrence of the disease [7]. Clinical lesions appearing on the skin are a very important indicator for primary diagnosis that needs to be supported by histopathological features and electron microscopy investigation [8]. A large number of publications reported polymerase chain reaction as a necessary tool in the diagnosis of bovine papilloma using consensus primers (FAP59/FAP64 and My09/MY11), which was designed based on human papillomavirus genome encoded in L1, L2, E6, and E7 structural proteins [9].…”
Section: Introductionmentioning
confidence: 99%
“…HPV E6 and E7 were shown to increase independently the induction of HIF-1α [65] or to interfere with HIF-1α degradation, leading to the inactivation of proteasomal degradation and to HIF-1α stabilization [39,72,73]. Moreover, built upon these evidences, and in light of the common biological functions of papillomavirus oncogenes [74], we may speculate that BPV oncoproteins could play a relevant role in regulation of HIF-1α pathway, contributing, at least in part, to the development of equine sarcoids by promoting HIF1α/VEGF mediated tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 92%
“…Thereby AhR-E2F1-KGFR signaling is actively involved in epithelial cell proliferation and early carcinogenesis. However, papilloma viruses are not just important for the development of human cancer but also a problem in veterinary medicine including for canines, felines and bovine species [49].…”
Section: Keratinasementioning
confidence: 99%